2019
DOI: 10.1002/jib.557
|View full text |Cite
|
Sign up to set email alerts
|

The application of metabolomics to ascertain the significance of prolonged maturation in the production of lager-style beers

Abstract: NMR-focused metabolomic analysis has been employed to ascertain the extent to which a diversity of non-volatile substances change in level during maturation and storage on a pilot and commercial scale. No substantive changes were observed, leading to the conclusion that, once materials such as vicinal diketones and acetaldehyde have been dealt with, there is no merit in the prolonged storage of beer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…It is not clear from this work (Masschelein 1986;Masschelein and Van de Meerssche, 1976) to what extent the authors are differentiating between the action of metabolism of viable yeast as opposed to autolysing yeast in delivering the supposed benefits of prolonged conditioning. Indeed, we should also compare these observations with those of others who applied metabolomics in finding no major difference in the level of a wide range of non-volatile substances between beer aged in the presence or absence of yeast, nor indeed any substantial changes in levels as compared to beer at the end of fermentation (Metrulas et al, 2019). This author suggests that the difference reflects the extent to which autolysis of yeast was occurring in the respective experiments in the two laboratories.…”
Section: Volatile Substancessupporting
confidence: 51%
“…It is not clear from this work (Masschelein 1986;Masschelein and Van de Meerssche, 1976) to what extent the authors are differentiating between the action of metabolism of viable yeast as opposed to autolysing yeast in delivering the supposed benefits of prolonged conditioning. Indeed, we should also compare these observations with those of others who applied metabolomics in finding no major difference in the level of a wide range of non-volatile substances between beer aged in the presence or absence of yeast, nor indeed any substantial changes in levels as compared to beer at the end of fermentation (Metrulas et al, 2019). This author suggests that the difference reflects the extent to which autolysis of yeast was occurring in the respective experiments in the two laboratories.…”
Section: Volatile Substancessupporting
confidence: 51%
“…As previously discussed, trigonelline (lower part of Figure 3 g) is among the most influential metabolites for distinguishing the pale lager group and the IPA group. Trigonelline is very interesting [ 19 , 43 , 56 ] and it has been recently identified in beer and described as a plant-associated metabolite whose concentration increases with boiling [ 43 ]. Hops are generally added right before boiling the beer wort, so that the alpha acids can be extracted from the raw hops and thermally isomerized into iso-alpha acids, giving the beer its characteristic bitter taste [ 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…An example of the MCR peak resolution and identification process is shown in Figure 1 , investigating the amino acid valine which is characterized by a quite complex spin system resulting in a symmetric multiplet. Its presence in beer was reported by many bibliographic sources [ 13 , 20 , 43 , 46 , 50 , 56 ], even though only Nord et al also reported its chemical shift and assignment [ 14 ]. In the example, four MCR models are shown: in each of them, it is possible to identify one resolved spectral profile that matches the actual complex signal of valine (in red in Figure 1 b–e), whose correct profile was recovered from the reference library of Chenomx ( Figure 1 f, a screenshot from the software’s interface).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the days of his employment within a brewing company that did not see the merits of prolonged aging of beer, the present author has been sceptical of its necessity. Laura Metrulas and colleagues used metabolomics to illustrate our inability to find significant changes in non‐volatile molecules in beers during prolonged storage . [We had previously explored the use of this technique to address impacts of late and dry hopping .]…”
Section: Flavourmentioning
confidence: 99%